PENGARUH METODE PEMBELAJARAN IKNKUIRI TERBIMBING BERBANTUAN MULTIMEDIA TERHADAP HASIL BELAJAR KIMIA SISWA KELAS XI IPA SMAN 1 SIKUR - Fena Prayunisa; Ermila Mahariyanti; Irwansah Irwansah (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
This study aims to determine the effect of guided inquiry learning methods on chemistry learning. Multimedia-assisted guided inquiry is that students are encouraged to be actively involved in the teaching and learning process. In order to provide proper visualization, tools are needed to stimulate it with temporal multimedia (audio, video and animation). This study used a quasi-experimental design (Quasy-Experimental) with a pretest-posttest control group design. The instruments used in this study were the lesson plan (RPP) and multiple choice test question sheets. Before the instrument is used in the sample, the instrument is tested first with a validity test, a reliability test, a discriminating power test, and a difficulty level test. The sample taken in this study is class XI IPA-1 using guided inquiry model assisted by multimedia and XI IPA-2 using conventional methods. The average chemistry learning outcomes of students in class XI IPA at SMA Negeri 1 Sikur who were taught with guided inquiry learning with multimedia assistance was higher than students who were taught using conventional methods, this can be seen from the average pretest score of the control class of 65.7 and the experimental class by 64.8. Then for the posttest results shown, the control class average score is 76.9 and for the experimental class 83.8. There is an effect of guided inquiry learning method with multimedia assistance on chemistry learning outcomes of class XI IPA students.